ANALISIS EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA KELAS IV DI SDN PASAR BARU 1 TANGERANG - Putri Rizkiyanah; Nur Latifah; Sumiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Competency standards for graduates at the Basic Education Level Education Unit are focused on: preparing students to become members of society who believe and are devoted to God Almighty and have noble character, cultivating character in accordance with Pancasila values, and growing students' literacy and numeracy competencies to pursue further education. Strengthening Character Education in elementary schools is optimized through programs organized through intracurricular, co-curricular and extracurricular activities. Character formation through extracurricular activities aims to strengthen the formation of students' personalities. The definition of extracurricular according to (Astitah, 2020) is that extracurricular activities are additional activities outside of class hours, whether carried out outside of school or at school, which have a vision to develop potential, talents and interests optimally, as well as grow independence, enrich and broaden knowledge horizons. and the abilities they have and can shape students' personalities or selves well. Through extracurricular activities, students can be polite in their daily lives and disciplined in implementing Islamic law.